Wellness Indices of Coast Guard Drill Instructors Toward the Development of a Health Management Program - Aceron, Eunice Maliao (Future Science / FSH-PH Publications, 2025)
Coast Guard Drill Instructors (CGDIs) play a vital role in shaping recruits into disciplined service members. However, the demanding nature of their profession can impact overall wellness, making it essential to assess and address health concerns to sustain both individual performance and organizational effectiveness. This study examined the wellness indices of CGDIs by evaluating their physical, mental, and emotional health and explored how demographic factors may influence these dimensions. The primary goal was to develop a tailored Health Management Program suited to their specific needs. A mixed-methods design was employed, integrating quantitative surveys with qualitative interviews. Standardized instruments—including the International Physical Activity Questionnaire (IPAQ), Depression Anxiety Stress Scales (DASS-21), and Emotional Style Questionnaire (ESQ)—were used to assess wellness levels. ANOVA was conducted to identify significant differences across demographic groups, while interviews with a PCG psychologist and selected military personnel provided richer contextual insights. Findings indicated that while the majority of CGDIs maintain stable mental health, a subset exhibited extreme symptoms of depression and anxiety, particularly CGDIs who are single, junior in rank and those assigned far distant from the place of residence. Despite the physically demanding nature of their duties, a significant level of sedentary behavior was reported. Emotional wellness was found to be moderate overall, with differences noted by age, birth order, and RTC assignment. The study resulted in the development of a comprehensive health program encompassing mental health support, physical activity, stress management, and spiritual counseling. ...